HUBUNGAN KECERDASAN EMOSIONAL DENGAN HASIL BELAJAR SISWA KELAS X JURUSAN TEKNIK BANGUNAN SMK NEGERI 5 PADANG - 126-132 . Arif Husnan (Universitas Negeri Padang, 2013)
This research is a correlation research that purposed to find the relationship between student grades of student in X class construction engineering SMKN 5 Padang. Population in this research is all students of X class construction engineering SMKN 5 Padang, school of year 2012/2013, which are amounted to 88 students. By using proportional random sampling technique, samples obtained are 72 students. The type of data that used in this research is primary and secondary data. Primary data is obtained from samples through questionnaire distribution about emotional intelligence, while secondary data is student grades which is obtained from dean of construction engineering class SMKN 5 Padang. Results of analysis show that there is a significant relationship between emotional intelligence and student grade for student in X class construction engineering SMKN 5 Padang on school of year 2012/2013. This outcome can be seen from result of t-test that is thitung ≥ ttabel (2.000). Key words : Kecerdasan emosional, hasil belajar